Termografia infravermelha na avaliação reprodutiva de touros girolando - Vanessa Amorim Teixeira (2018)
The objective was to evaluate the semen quality of Girolando bulls from different racial compositions and to correlate it with infrared thermography. A total of 64 bulls 3/4 Dutch + 1/4 Gir (3/4 HOL) and 64 bulls 5/8 Dutch + 3/8 Gir (5/8 HOL) were evaluated, with 28.1 ± 6.61 months of age and 579 ± 125 kg live weight. The andrological classification by points considered scoring indices for motility, vigor, sperm morphology, scrotal circumference and age. Infrared thermography was performed in the ocular and scrotal anatomical regions. For the evaluation of the thermoregulation capacity of the bulls, the difference () between the ambient temperature and the rectal temperature and the T ° of the environment, maximum temperatures of the eye and scrotum, and difference in the temperatures of the most dorsal and ventral line of the scrotum (DIF L1 - L2). The evaluation of the effect of the genetic composition was performed using a linear mixed model, considering the fixed effect of the genetic composition and the random effect of the year of evaluation. The Spearman rank correlation coefficient was used to associate the thermography data with the reproductive parameters. The significance of the effect of genetic composition was considered adopting equal to 0.05. It was verified that thermoregulation capacity interferes in the reproductive efficiency of the Girolando bulls, regardless of the racial composition (DIF L1 - L2, P <0.0001, for both racial groups), however in the environmental conditions occurred during the execution of this experiment, the composition racial relationship was more important for the definition of semen quality than the ability to regulate the temperature of the scrotum. Racial composition more strongly influenced the major defects (DMAI) (P <0.0001 for 5/8 HOL when compared to 3/4 HOL) and rectal and minor scrotal temperatures (DMEN) (P <0.0001) of spermatozoa. Bulls 3/4 HOL have superior reproductive characteristics and body morphology in relation to 5/8 HOL bulls, which in turn presented a greater thermoregulation capacity of the scrotal temperature. The results indicate that infrared thermography can be used as an alternative non - invasive and complementary method in the reproductive evaluation of bulls, with relation to sperm concentration and morphological characteristics of spermatozoa.